Lithuanian Books in Exhibitions Abroad in the Period of 1895–1940 - Starkūnaitė, Vanda (Knygotyra, 1973)
Lithuanian books represent our country, its national culture not only in the Soviet Union but also abroad. The recognition of Lithuanian books which has recently been widely mirrored in Soviet as well as foreign press, a great number of prizes and diplomas, won at international exhibitions, was not an easy gain. The road to the wide acclaim lay through long traditions; in that not a little role was played by book exhibitions. It is interesting, therefore, to survey the history of book exhibitions.It was only at the end of the 19th century that Lithuanian books gained access to exhibitions. The delay can be accounted for by the fact that Lithuanian printing in Latin characters had been abolished for a long time. Progressive cultural workers fought for the re-establishment of Lithuanian printing; in that struggle book exhibitions played not an insiguitificant role. In 1895 from February 19 to June 15 a book exhibition was held in St. Petersburg were on the initiative of E. Volter, S. Baltramaitis and others, more than 100 Lithuanian publications were on display. The exhibition was meant to attract the attention of Russian society to the absurdity of abolition of printing and thus gain support in the struggle against it.The 1900 World Exhibition in Paris was another arena where the battle for Lithuanian books was fought. It was not an easy task to collect books for the exhibition where we find 563 Lithuanian books. Beside the books Lithuanian etnographic exhibits were on display. This exhibition greatly contributed to the re-establishment of Lithuanian printing in 1904. But in its further way Lithuanian books met with great difficulties: socialpolitical atmosphere of the country was not very conducive to the publishing business, let alone book exhibitions.In the newly formed Lithuanian bourgeois state book exhibitions were the concern of private people. There were cases when Lithuanian books were exhibited in the exhibitions of Catholic Books abroad: in Lille in 1932 and in Vatican in 1936.In 1922 and 1933 Lithuanian books were exhibited in Prague. In 1930 a few Lithuanian books were shown in the exhibition of Lithuanian folk art in Goeteborg (Sweden). There were already 10 Lithuanian publications in the 1933 World Exhibition in America. At that time there were no book contests, but the participation in the exhibitions fostered the care for the quality of publishing and poligraphic execution.A very important work in the publishing of Lithuanian books and their edition was carried out by a group of enthusiasts who in 1931 formed the “Society of 27 Book Lovers”. Thanks to their efforts the 1937 World Exhibition in Paris was an important event in Lithuanian cultural life too. The Society issued several publications specially for the exhibition. 6 of them won the Grand Prix – that was the first recognition won by Lithuanian books.In 1938 Lithuanian books were exhibited in Prague, in 1939 – in the World exhibition in New York.Very important was the exhibition held in 1940 in Moscow. More than 1,000 books on various questions, booklets and magazines were shown at it. This exhibition contributed to the further cultural friendship and collaboration between the two neighbouring countries.In the period of 1895–1940 Lithuanian books could often be seen at different exhibitions. Though of varied quality, their poligraphic execution receives acclaim and the Grand Prix proves the high quality of our publishing mastery though the school of Lithuanian artists-book illustrators was still in the make.